Evaluation of the impact of moist convection on the development of asymmetric inner core instabilities in simulated tropical cyclones. (14th November 2014) - Naylor, Jason; Schecter, David A.
Abstract This paper examines the nature and consequences of inner core instabilities in several intense tropical cyclones (TCs) simulated with a cloud‐resolving numerical model. The initial wave growth leading to polygonal eyewalls and mesovortices in each TC is shown to closely resemble that found in a dry nonconvective vortex with the same primary circulation. Such agreement is reasonable partly because the bulk of the cloudy eyewall updraft is outside the vorticity ring in which the instability occurs. An energetic analysis of the TC instability verifies that the symmetric secondary circulation contributes relatively little to the early growth of eddy kinetic energy. On a longer time scale, isentropic potential vorticity mixing triggered by the instability irreversibly reduces the maximum wind speed of the dry vortex. In the more realistically simulated TC, moist convection modulates the mixing and regenerates the broken vorticity ring. Eventually, the maximum wind speed of the TC and the local parameters that determine its theoretical magnitude return to within a few percent of their preinstability values. It is found that the time scale for wind speed restoration is sensitive to the surface drag coefficient. The long‐term effects of inner core instability on precipitation are briefly addressed.